2019
DOI: 10.3390/jcm8071078
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Hearing Loss and the Prevalences of Cataract, Glaucoma, Diabetic Retinopathy, and Age-Related Macular Degeneration in Korea

Abstract: This study was conducted using the database of the Korea National Health and Nutrition Examination Survey to determine whether age-related eye diseases such as cataract, glaucoma, diabetic retinopathy (DR), and age-related macular degeneration (AMD), are related to hearing loss. 12,899 participants ≥ 40 years of age were included. The weighted prevalence of diabetic retinopathy was not significantly different between the normal hearing group and hearing-impaired group, but the weighted prevalences of cataract,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…These findings clearly support the role of microcirculation alterations in ARHL pathways. Moreover, diabetes mellitus and glycemic abnormalities could be related to alterations of microvessel metabolism and may be considered the prominent risk factor for age-related conditions such as ARHL or macular abnormalities [43]. However, we could not find such relations in our study.…”
Section: Discussioncontrasting
confidence: 76%
“…These findings clearly support the role of microcirculation alterations in ARHL pathways. Moreover, diabetes mellitus and glycemic abnormalities could be related to alterations of microvessel metabolism and may be considered the prominent risk factor for age-related conditions such as ARHL or macular abnormalities [43]. However, we could not find such relations in our study.…”
Section: Discussioncontrasting
confidence: 76%
“…As an age-related disease, the cataract afflicted population coincides with those hard-of-hearing ( 19 ). Masks are essential to prevent transmission, but pose challenges to persons hard-of-hearing, as they reduce acoustic transmission and prevent lip reading ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study used Western data and did not target patients with diabetes. There was a population-based study including Asians, which reported that the prevalence of DR was not significantly different between the normal hearing group and hearing loss group [ 24 ]. They did not classify DR according to severity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have included several related factors that may affect hearing loss in patients with DM, as suggested in previous studies [ 20 , 21 , 22 , 23 , 24 ]. From the KNHANES databases, we collected data regarding various factors obtained through direct interviews using standardized questionnaires.…”
Section: Methodsmentioning
confidence: 99%